ON THE STUDY OF PHYSICOCHEMICAL PROPERTIES OF SOILS IN THE REGIONS OF THE REPUBLIC - Shamuratova, Moxinabonu; Giyasidinov, Abduaziz; Eshmetov, Izzat; Nurjanova, Gulnoza (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
In the case of increasing anthropogenic load and changing climate factors, the study of the physical properties of soils in various regions of the Republic is becoming especially relevant. Particular emphasis is placed on the parameters of water-holding capacity, sorption ability, bulk density, and porosity, as these factors play a decisive role in the productivity of agroecosystems and the stability of land resources. In this study, a detailed analysis of serozem and saline soils was performed using desiccator-based water vapor sorption isotherm techniques, complemented by the application of structure-modifying additives of organic and polymeric nature. Various doses of additives (sulfonyl and carboxymethyl cellulose) were used in varying doses for 50 g of air-dry soil in the experimental part. An increase in specific surface area and porosity is achieved by adding it, but sulfonyl and its composite systems have a more noticeable impact on capillary moisture. The comparative analysis revealed that optimal dosages provide an increase in moisture capacity of up to 20-25% compared to control samples. Therefore, the obtained results contribute not only to a deeper understanding of the physical properties of soils but also provide practical guidance on the application of organic additives aimed at improving agronomic qualities and increasing the efficiency of reclamation measures under the conditions of the Republic.